The Determinants of Capital Structure Choice - TITMAN, SHERIDAN; WESSELS, ROBERTO (Journal of Finance, 1988)
ABSTRACT This paper analyzes the explanatory power of some of the recent theories of optimal capital structure. The study extends empirical work on capital structure theory in three ways. First, it examines a much broader set of capital structure theories, many of which have not previously been analyzed empirically. Second, since the theories have different empirical implications in regard to different types of debt instruments, the authors analyze measures of short‐term, long‐term, and convertible debt rather than an aggregate measure of total debt. Third, the study uses a factor‐analytic technique that mitigates the measurement problems encountered when working with proxy variables.